2017
DOI: 10.1038/s41467-017-00305-0
|View full text |Cite
|
Sign up to set email alerts
|

Human microcephaly protein RTTN interacts with STIL and is required to build full-length centrioles

Abstract: Mutations in many centriolar protein-encoding genes cause primary microcephaly. Using super-resolution and electron microscopy, we find that the human microcephaly protein, RTTN, is recruited to the proximal end of the procentriole at early S phase, and is located at the inner luminal walls of centrioles. Further studies demonstrate that RTTN directly interacts with STIL and acts downstream of STIL-mediated centriole assembly. CRISPR/Cas9-mediated RTTN gene knockout in p53-deficient cells induce amplification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(95 citation statements)
references
References 52 publications
5
90
0
Order By: Relevance
“…Centriole duplication [58,59] Cell proliferation, cell cycle G2/M phase and apoptosis (GC) [32] Centromere assembly [60] Cell proliferation and apoptosis (prostate cancer, PCa) [28] Cell cycle and chromosomal segregation [61] DNA repair (OC) [62] MCPH8 (CEP135)…”
Section: Mcph3 (Cdk5rap2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Centriole duplication [58,59] Cell proliferation, cell cycle G2/M phase and apoptosis (GC) [32] Centromere assembly [60] Cell proliferation and apoptosis (prostate cancer, PCa) [28] Cell cycle and chromosomal segregation [61] DNA repair (OC) [62] MCPH8 (CEP135)…”
Section: Mcph3 (Cdk5rap2)mentioning
confidence: 99%
“…This regulates the replication of centrioles in vivo [58]. Other studies have shown that the human microcephalic malformation protein rotatin (RTTN) directly interacts with STIL and acts downstream of STIL-mediated centrosome assembly [60], thereby affecting the development of the brain. MCPH8 (CEP135) is particularly important in the assembly, amplification, and microtubule binding of the centriole [99].…”
Section: The Centrosomal Root Of Mcph Genesmentioning
confidence: 99%
“…Further, human POC5 (hPOC5) was found to be enriched in the distal portion of human centrioles, where it has an essential role in centriole elongation and maturation (Azimzadeh et al, 2009). This role for hPOC5 is notable because molecular mechanisms that contribute to building a full-length centriole/BB remain poorly understood, especially compared with the mechanistic and molecular understanding of early assembly (Chang et al, 2016; Chen et al, 2017; Comartin et al, 2013; Keller et al, 2009; Schmidt et al, 2009). Furthermore, a truncating mutation in hPOC5 was recently implicated in an inherited form of retinal degeneration, retinitis pigmentosa, characterized by progressive loss of photoreceptors, and Poc5 was found to colocalize with centrin in the connecting cilium of zebrafish photoreceptors, where it is important for normal retinal development and function (Weisz Hubshman et al, 2018; Wheway et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, biallelic RTTN variants have been associated with rare cases of polymicrogyria, malformation of the developing cerebral cortex and seizures (Kheradmand Kia et al, ), microcephalic primordial dwarfism (Shamseldin et al, ), and simplified gyri (Chartier et al, ). The human RTTN gene (MIM# 610436) encodes Rotatin, a large centrosomal protein that interacts with the centriolar protein STIL for appropriate assembly of full‐length centrioles (Chen et al, ). To date, 15 cases belonging to eight families have been described with biallelic variants in the RTTN gene, neurodevelopmental delay, and variable associated features (Grandone et al, ; Stouffs et al, ; Wambach et al, ).…”
mentioning
confidence: 99%
“…Rotatin is essential for building full‐length centrioles forming basal bodies of cilia as well as nucleation points for spindle formation during cell division (Chen et al, ). In humans, the importance of Rotatin for neural proliferation, cortical organization, and growth is shown by the identification of RTTN variants in patients with polymicrogyria (Kheradmand Kia et al, ) or with microcephaly and primordial dwarfism (Shamseldin et al, ).…”
mentioning
confidence: 99%